THE LEARNING OF POEM WRITING BY IMPLEMENTING PROJECT-BASED LEARNING FOR 8TH GRADE STUDENTS - Fiona Desty Punusingon; Intama J. Polii; Viktory N. J. Rotty (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The purpose of this study is to describe the experiences of eighth-grade junior high school students who use Project Based Learning as a paradigm for learning to write poems. This study was also organized to see the implementation of the Project Based Learning model in learning to write poetry for eighth-grade junior high school students. This research was conducted at SMP Kristen Taraitak and was organized using an analytic descriptive approach. The participants in this study were 22 eighth-grade students from SMP Kristen Taraitak. Data were collected using methods including interviews, surveys, and testing. The percentage method was used to analyze the data. Findings from the Project Based Learning method for teaching poetry writing Students in grade VIII of SMP Kristen Taraitak were considered "competent" because their average scores were in the 80-89 percentile. Thus, the use of the Project Based Learning model is one of the right and suitable steps for teachers to improve the learning process of writing poetry, which certainly brings many benefits to students' development in learning to write, especially in terms of learning to write poetry for class VIII students of SMP Kristen Taraitak.